Towards A Structural Judicial Approach in The Egyptian Administrative Courts: Proportionality as A Practical Solution - Rashdan, Mohab Ali (AUC Knowledge Fountain, 2023)
The lack of detailed and explicit law provisions governing human rights cases obliges judges to fill this legal gap by applying generic constitutional articles. Now that all human rights are interdependent and overlapping, they practically conflict with each other. Therefore, Egyptian judges are obliged to issue a decision in these cases despite such tensions, taking into consideration the lack of detailed and explicit law provisions regulating these disputes. The question here concerns the criteria that the administrative courts should adopt when overseeing administrative decisions to judge in a case when there are two or more disputing and conflicting interests organized by several constitutional articles with no plain or detailed legislation drawing their correlation and limitations. Realistically, the Egyptian administrative courts have applied various and disparate judicial approaches such as legitimacy, suitability, necessity, gross error in the assessment, and comparison between benefits and harms. The concern is that applying different methodologies may lead to different conclusions. This paper argues that using proportionality through its four degrees may unite the mechanism of judicial review, reconcile constitutional values to avoid a hierarchy amongst them, organize the mind of judges, and raise transparency within courts.